2000
DOI: 10.1038/sj.bjp.0703110
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of BIBN4096BS, the first selective small molecule CGRP antagonist

Abstract: Calcitonin gene-related peptide (CGRP) is one of the most potent endogenous vasodilators known. This peptide is increased during migraine attacks and has been implicated in the pathogenesis of migraine headache. Here we report on the ®rst small molecule selective CGRP antagonist: BIBN4096BS. In vitro, this compound is extremely potent at primate CGRP receptors exhibiting an a nity (K i ) for human CGRP receptors of 14.4+6.3 (n=4) pM. In an in vivo model, BIBN4096BS in doses between 1 and 30 mg kg 71 (i.v.) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
347
1
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(370 citation statements)
references
References 17 publications
(18 reference statements)
17
347
1
5
Order By: Relevance
“…An important breakthrough in the field of CGRP was the development of the potent and selective CGRP receptor antagonist olcegepant (BIBN4096BS; Doods et al 2000). In in vivo animal models of migraine, olcegepant attenuated the vasodilation induced by trigeminal stimulation and capsaicin-induced carotid arteriovenous anastomotic dilatation Edvinsson 2004;Kapoor et al 2003;Petersen et al 2005b).…”
Section: Cgrp Receptorsmentioning
confidence: 99%
“…An important breakthrough in the field of CGRP was the development of the potent and selective CGRP receptor antagonist olcegepant (BIBN4096BS; Doods et al 2000). In in vivo animal models of migraine, olcegepant attenuated the vasodilation induced by trigeminal stimulation and capsaicin-induced carotid arteriovenous anastomotic dilatation Edvinsson 2004;Kapoor et al 2003;Petersen et al 2005b).…”
Section: Cgrp Receptorsmentioning
confidence: 99%
“…More recently, Grant et al (2004) reported that exogenously administered haCGRP triggers, in the arterial mesenteric bed of the mouse, a marked vasodilatation which was abolished by BIBN4096BS (1-piperidinecarboxamide, N-[2- [ [5-amino-1-[ [4-(4- (Doods et al, 2000). It is however worthy of mention that the contribution of the endothelium in these vasoactive responses to CGRP in the mouse mesenteric circuit was not explored by this group.…”
Section: Introductionmentioning
confidence: 99%
“…Doods et al [71] described the first potent and selective non-peptide human CGRP-receptor antagonist (RA): BIBN4096BS, later renamed olcegepant. Prior to that, N-terminal-truncated CGRP fragments have been described as antagonists, but with limited use in vivo because of their short half-life, lower affinity, and non-selectiveness [20,72].…”
Section: Cgrp Receptor Antagonistsmentioning
confidence: 99%